ЗҮҮН АЗИЙН ЗАРИМ ОРНЫ ХӨГЖЛИЙН ТУРШЛАГА БА МОНГОЛ УЛСЫН ТӨРИЙН БОДЛОГО - Ё.Довчин; Ч.Өлзийсайхан (Politology, 2023)
The article "History of the development of East Asian countries and the Mongolian government’s strategy" discusses how Japan, South Korea and other Asian giants have relied on their sources rather than loans and financing from off shore for their growth of the economy. The government of those countries were more keen to develop their national corporates which led the countries to a more fruitful state. However, the Mongolian government is not taking careful steps in protecting their sectors, especially those of strategically important sectors.